2020
DOI: 10.6023/cjoc202005066
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light Photocatalytic Remote Halo-difluoroalkylation of Thioalkynes

Abstract: Fluoroalkylated alkenes are of significant importance in life sciences and functional materials. The fluoroalkylation of alkynes offers an efficient method for the synthesis of functionalized fluoroalkylated alkenes. However, the current methods are often limited to 1,2-difunctionalization, while the remote fluoroalkylative difunctionalization of alkynes has been rarely developed. Herein, a novel visible-light-induced remote halo-difluoroalkylation of thioalkynes is realized with difluoroalkyl halides as the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The authors demonstrated this strategy in the remote ketofluoroalkylation, hydroxytrifluoromethylation, and bromofluoroalkylation of heteroalkynes (Scheme 24b). 54 The mechanisms for these reactions were proposed as follows. The reduction of Umemoto's reagent or fluoroalkyl halides by excited photocatalysts provided a fluoroalkyl radical.…”
Section: Direct Functionalizationmentioning
confidence: 99%
“…The authors demonstrated this strategy in the remote ketofluoroalkylation, hydroxytrifluoromethylation, and bromofluoroalkylation of heteroalkynes (Scheme 24b). 54 The mechanisms for these reactions were proposed as follows. The reduction of Umemoto's reagent or fluoroalkyl halides by excited photocatalysts provided a fluoroalkyl radical.…”
Section: Direct Functionalizationmentioning
confidence: 99%
“…[111,112] Under photocatalytic reaction conditions, 1,5-HAT-mediated halogen transfer allows for a more complex radical cascade (Scheme 13b). [111,112] Regarding metal-catalyzed processes, it is to be noted that alkynyl sulfides predominantly exhibit high reactivity in the form of cationic intermediates (Scheme 14). This property has been applied in both intermolecular [113] and intramolecular hydroarylation reactions of alkynes.…”
Section: S-activated Alkynesmentioning
confidence: 99%
“…[110] In addition to effective stabilization of cationic intermediates, alkynyl sulfides are excellent traps for electrophilic radicals and are capable of maintaining a halogen transfer radical addition chain reaction (Scheme 13a). [111,112] Under photocatalytic reaction conditions, 1,5-HAT-mediated halogen transfer allows for a more complex radical cascade (Scheme 13b). [111,112] Regarding metal-catalyzed processes, it is to be noted that alkynyl sulfides predominantly exhibit high reactivity in the form of cationic intermediates (Scheme 14).…”
Section: S-activated Alkynesmentioning
confidence: 99%